2022
DOI: 10.3389/fspor.2022.842192
|View full text |Cite
|
Sign up to set email alerts
|

GRADE IT—A Literacy-Based Assessment Tool for Generating Research-Based Assessment Data to Evidence the ImpacT of Anti-doping Education via Athletes' Capability to Make the Right Decision

Abstract: The International Standard for Education (ISE) mandates Code Signatories to plan, deliver, and evaluate anti-doping education. Performance-based evaluation of anti-doping education requires alignment between educational goals, content, and defined outcomes. Based on an existentialist teaching and learning philosophy, we aimed to develop and test an anti-doping impact evaluation tool, to assess the impact of anti-doping education on doping awareness, literacy (DAL), perceived trust, and legitimacy. We propose t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
2
0
1
Order By: Relevance
“…Comprehensive ADE is consistent with claims strongly associated with trustworthiness and legitimacy (Blank et al, 2022 ). Most athletes desire clean sporting behavior free of doping and need ADE to reinforce the commitment to clean sport rather than to prevent doping (Blank et al, 2022 ), so a multifaceted ADE goes beyond information-based knowledge to promote compliance with the Code and to develop decision-making and practical skills.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…Comprehensive ADE is consistent with claims strongly associated with trustworthiness and legitimacy (Blank et al, 2022 ). Most athletes desire clean sporting behavior free of doping and need ADE to reinforce the commitment to clean sport rather than to prevent doping (Blank et al, 2022 ), so a multifaceted ADE goes beyond information-based knowledge to promote compliance with the Code and to develop decision-making and practical skills.…”
Section: Introductionsupporting
confidence: 74%
“…An extensive survey assessing perceptions of ADE among elite youth athletes found that those with selective educational experiences had higher perceptions of the usefulness and reliability of ADE than athletes who were provided with information-based ADE (Gatterer et al, 2021). Comprehensive ADE is consistent with claims strongly associated with trustworthiness and legitimacy (Blank et al, 2022). Most athletes desire clean sporting behavior free of doping and need ADE to reinforce the commitment to clean sport rather than to prevent doping (Blank et al, 2022), so a multifaceted ADE goes beyond information-based knowledge to promote compliance with the Code and to develop decisionmaking and practical skills.…”
Section: Introductionmentioning
confidence: 94%
“…Research on Australian interventions among community sports clubs have shown effectiveness on behavioral outcomes ( 25 ), as well as cost-effectiveness ( 26 , 27 ). Nevertheless, scant research has targeted NSFs ( 28 , 29 ), and focused principally on programs dedicated to health topics, such as, safeguarding children ( 30 ), doping prevention ( 31 , 32 ) and injury prevention ( 33 ). The presence, albeit limited, and the narrow awareness of HP as a global concept in international or NSF has been demonstrated ( 34 ), and its alignment to sports federation business is crucial for further investment ( 28 , 35 ).…”
Section: Introductionmentioning
confidence: 99%
“…Isto cresce ainda mais de importância ao considerarmos que estudos apontam para a desinformação de boa parte de atletas jovens. Blank et al (2022) avaliaram 1255 jovens atletas austríacos de elite e concluíram que 25.1% nunca haviam recebido nenhuma educação anti-doping. Além disto, Peters, Schulz, Oberhoffer, & Michna (2009), em estudo realizado na Alemanha, sugeriram que 75.3% dos atletas avaliados por questionário autorrespondido já haviam pensado em utilizar substâncias ou métodos proibidos.…”
Section: Discussionunclassified